Information retrieval with concept ontology for domain-specific text - Li, Haihui (2017)
In an age of information boom, efficient retrieval of information is becoming more important. Enormous amount of information can sometimes cause over-load for people. Moreover, traditional search engines only return users with a ranked list of documents without a grand overview of information. To address users' growing information needs, we proposed an information retrieval solution with the use of concept ontology. By integrating information retrieval with ontology, users can effectively navigate among different documents and have a quick grasp of the information contained in the documents.